Kant’s Nonconceptual View on Imagination and its Role in Cognition - de Sá Pereira, Roberto Horácio (Con-Textos Kantianos. International Journal of Philosophy, 2024)
This paper meticulously examines the debate about the autonomy/independence of the imagination as understood by Kant. In contrast to the prevailing intellectualist interpretation, which postulates the dependence of the imagination on understanding, this paper presents comprehensive historical and systematic objections. It claims that understanding does not provide conditions for us to represent something as an object in our sensibility (the traditional conceptual mainstream reading of Kant). Instead, it only provides conditions for us to recognize that we represent something as an object in our sensibility. The essay confidently claims that Kant's exercise of the imagination remains independent of understanding across both editions of the Critique. It suggests that the rules of the understanding impose constraints on the imagination only when the understanding recognizes something as an object. I refer to this as Kant’s nonconceptual of imagination in cognition